THE MECHANISM OF INCREASING THE PROFESSIONAL TRAINING OF FUTURE PHYSICAL EDUCATION TEACHERS THROUGH RHYTHMIC GYMNASTICS TOOLS - Xaitbayeva Barnoxon Baxodirovna (Proximus Journal Publishing, 2024)
The article is devoted to the study of mechanisms for improving the professional training of future physical education teachers using rhythmic gymnastics. The author analyzes the role of rhythmic gymnastics as a tool for improving professional skills and physical training of students of pedagogical universities. The paper examines the key aspects of the development of coordination, flexibility and strength, as well as the formation of pedagogical competencies necessary for effective teaching of physical culture. The main attention is paid to the substantiation of methodological approaches aimed at improving educational programs that contribute to the adaptation of students to professional activities. The results obtained confirm that the use of rhythmic gymnastics contributes to the comprehensive development of the necessary competencies of future physical education teachers, which increases their readiness to work in an educational environment.
Keywords: professional training; rhythmic gymnastics; physical culture pedagogical competencies